Hematological parameters in two neotropical freshwater teleost, Leporinus macrocephalus (Anostomidae) and Prochilodus lineatus (Prochilodontidae) - Tavares-Dias, Marcos; Moraes, Flávio Ruas de [UNESP]; Imoto, Mizue Egami (Universidade Federal de Uberlândia (UFU), 2008)
Leporinus macrocephalus is a non-migratory omnivore fish which occurs in waters with a relatively high oxygen rate. Prochilodus lineatus is a migratory fish that inhabits deoxygenated hypolimnion and feeds on detritus material. Red blood cell, thrombocytes and white blood cell counts, hematocrit and hemoglobin, serum electrolytes (sodium, potassium, calcium, magnesium and chloride), metabolic products (total serum protein and plasma glucose) and blood cells major axis length for L. macrocephalus and P. lineatus were compared. White blood cell counts for both species indicated a similar activity of the immune functions. The concentration of total protein, sodium, calcium, magnesium and chloride, MCV, as well as red blood cells, monocytes, and thrombocytes size in L. macrocephalus were higher than in P. lineatus. However, P. lineatus had higher red blood cell counts, hematocrit and hemoglobin, which reflects a considerable adaptation to survive in an environment with low levels of oxygen.
Keywords: Blood; Leukocytes; Metabolism; freshwater fish; Hematology; Leporinus macrocephalus; Prochilodus lineatus